U źródeł mitu o dobrym cesarzu. Przyczynek polsko-węgierski - Woźniak, Krzysztof Paweł (Zeszyty Wiejskie, 2010)
Among the long existing historical stories about the good emperor, deriving from the southern Malopolska folk tradition, the most outstanding are the ones concerning the good emperor who freed the folk from the serfdom. The monarch‟s deed was supposed to be the result of his former experiences. The figure of a just, gracious and caring ruler was commonly associated with the Habsburg monarchs: Franz II, Franz Joseph, the crown prince Rudolph Habsburg. Confronting the content of the above mentioned stories with the original sources from the region of the southern Carpathia mountains presented that the basis of the myth concerning the good monarch from Vienna was the story about the Matthias Corvinus who ruled Hungary in the 15th century. As early as in the 16th century the caring king Matthew myth was spread all over the huge, at the time, Hungarian land. The story became known on the Polish territory, coming through the Slovakian border, approximately on the turn of the 18th and the 19th century.